Comparative extraction processes, volatile compounds analysis and antioxidant activities of essential oils from Cirsium japonicum Fisch. ex DC and Cirsium setosum (Willd.) M.Bieb. (May 2016) - Zeng, Qiao-Hui; Zhao, Jiang-Bin; Wang, Jing-Jing; Zhang, Xue-Wu; Jiang, Jian-Guo
Abstract: A comparison of extraction processes, volatile compounds analysis and antioxidant activities of essential oils (EOs) from Cirsium japonicum Fisch. ex DC and Cirsium setosum (Willd.) M.Bieb., two morphological and aroma similar species, were investigated. In total, 143 different constituents were assigned, which were further grouped into hydrocarbons, alcohols, esters, ketones, carboxylic acids, aldehydes, aromatics. Results of HS-SPME revealed that the similar grassy and fruity aromas of C. japonicum and C. setosum derived from Hexyl alcohol, 1-Pentanol, 6, 10, 14-trimethyl-2-Pentadecanone, etc. In addition, HD was employed to gather EOs. Compared with the Standard Method, yields of EOs by the Optimum Method from C. japonicum and C. setosum increased by 86.58 ± 4.28% and 102.60 ± 1.57%, respectively. Chemical analysis by GC–MS revealed that the high temperature of the optimal condition decreased the types of EOs compounds or changed some compounds into other hot-steady compounds. Furthermore, antioxidant activity analysis (DPPH, ABTS, and FRAP assays) indicated that EOs extracting by the optimized condition of both C. japonicum and C. setosum possessed much higher FRAP value and potent ABTS radical scavenging ability. Therefore, the study could pave the way for the extraction of EOs and further developing of C. japonicum and C. setosum resources. Highlights: The extraction apparatus of HD was improved, and yields of EOs raised. 143 volatile components and 18 of which were identified from Cirsium japonicum and Cirsium setosum . Yields of EOs from C. japonicum and C. setosum increased by 86.58% and 102.60%. EOs of C. japonicum and C. setosum had strong reducing and ABTS radical scavenging ability.